Językowy obraz konia w polszczyźnie jako wyraz tradycji wspólnoty szlacheckiej = Linguistic picture of a horse in the Polish language as an expression of the noble community tradition - Szagun, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the linguistic picture of a horse in the Polish language by the nineteenth century as a significant element of the traditions of the noble community, strongly influencing the consciousness of the nobility and culture of the period of Nobles` Republic which traces we observe in contemporary Polish language and culture.
Keywords: koń; szlachta; leksyka; frazeologizm; przysłowie; maść; koń wierzchowy; prestiż; tożsamość; malarstwo; literatura; horse; Nobility; vocabulary; idiom; saying; ointment; saddle horse; prestige; identity; painting; literature